The wife’s disagreement with the heirs regarding the option inheritance - Adel Jassim Al-Wahili; Dr. Mohammad Taqi Fakhlaei; Dr. Mohammad Hassan Ha'iri (Journal of College of Education, 2024)
The conclusion of the research is that the research addresses a jurisprudential issue, regarding the inheritance of the option, as the option is an inherited right as has been proven in its place, and it is summed up by the disagreement between the heirs and the wife regarding whether or not to annul the option, since annulment and its failure to cause harm and harm to the various parties, which requires a solution, and since the solution cannot be Except by mutual consent, and because mutual consent leads to differences in shares and proportions, which is usually thorny, and they may differ in increase and decrease, and because of the large number of assumptions, since the issue is not personal, but rather a general problem, and it occurs in types of assumptions and differences in shares and numbers that represent the shares, so the problem needs an equation. A general mathematical formula that solves any problem of this type, regardless of its assumptions or numbers. It is a new equation that has not been presented previously and can be used in disputes of this type. It is not at the level of a fatwa, but rather pure scientific research and a fair solution to a problem
Keywords: Heritage: Heritage in language: Heritage with kasrah, its origin is inheritance, derived from (warith), the waw was replaced with a hamzah and a ta' so it became inheritance and heritage, and likewise the ya' of inheritance (Ibn Abada)